Effect of supplementing encapsulated microbial enzymes to corn-soybean meal based pelleted diets on performance and carcass variables in coloured broiler chicken - PRAKASH, B; RAO, S V RAMA; NRAJU, M V L; REDDY, KKONDAL; AKPANDA, AKPANDA; REDDY, P V MALLIKARJUNA (The Indian Journal of Animal Sciences, 2016)
The experiment was conducted to determine the dietary supplementation of encapsulated (EC) or UEC enzymes on performance of colour broilers. The dietary supplementation of EC polysaccharide hydrolyzing enzymes and protease improved the performance compared to other groups. Feeding the birds with low nutrient-density diets did not affect the performance of the coloured broilers. The supplementation of EC enzymes resulted in a decrease in abdominal fat and increase in ready to cook yield compared to those diets with UEC or without enzymes.